Atmospheric Degradation of Acetic Anhydride. Kinetic Study and Reaction Mechanism - Vila, Jesús A.; Rimondino, Guido N.; Peláez, Walter J.; Kalinowski, Mateo; Malanca, Fabio E. (2024)
This is a preprint article, it offers immediate access but has not been peer reviewed.